2014
DOI: 10.3109/13816810.2014.946056
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmologic Impairment during Adulthood in Central Congenital Hypoventilation Syndrome: A Longitudinal Cohort Analysis of Nine Patients

Abstract: This study allowed the description of ophthalmologic abnormalities occurring in CCHS in a series of adult patients, thus improving current knowledge of the disease. The prevalence of pupillary and iris lesions were lower than those observed in a series of children, suggesting that they could be considered as systemic disease severity markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 10 publications
1
9
0
1
Order By: Relevance
“…A recent study revealed the presence of strabismus, pupillary, and iris abnormalities in CCHS adults. 43 In this cohort, the prevalence of pupillary and iris abnormalities was less compared to children, indicating their potential role as systemic disease severity marker. 43 …”
Section: Phox2b and Respiratory Controlmentioning
confidence: 68%
See 1 more Smart Citation
“…A recent study revealed the presence of strabismus, pupillary, and iris abnormalities in CCHS adults. 43 In this cohort, the prevalence of pupillary and iris abnormalities was less compared to children, indicating their potential role as systemic disease severity marker. 43 …”
Section: Phox2b and Respiratory Controlmentioning
confidence: 68%
“…CCHS is not just a disorder of respiratory control. Affected patients may have associated conditions due to ANS dysfunction including tumors of neural crest origin (neuroblastoma, ganglioneuroma, and ganglioneuroblastoma) 6 , 30 32 gastroin testinal manifestations such as esophageal dysmotility, 14 , 33 constipation, 14 aganglionic megacolon Hirschsprung’s disease (HSCR), 1 , 6 , 14 , 34 and other signs and symptoms attributed to abnormal development of neural crest cells such as cardiovascular, 25 , 35 39 ophthalmologic, 14 , 40 – 43 endocrinologic, 44 48 and temperature regulation abnormalities. 49 CCHS patients may have dizziness and syncopal episodes due to cardiac rhythm or blood pressure control abnormalities.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Three patients had documented mild-to-moderate pulmonary artery hypertension, five had gastroesophageal reflux requiring medical treatment, two had Hirschsprung’s disease (having required extensive colectomy in one case). Two patients had undergone strabismus corrective surgery, five suffered from convergence deficiency, and six had refraction abnormalities (some of these patients have been described in [ 12 ]).…”
Section: Methodsmentioning
confidence: 99%
“…Ventilatory support notably affects the patient’s and family’s lifestyle [ 8 ]. In addition, CCHS patients may present cardiac conduction disorders [ 7 , 9 , 10 ], severe constipation with Hirschsprung’s disease [ 7 ], gastroesophageal reflux, thermal dysregulation, orthostatic hypotension [ 11 ], ophthalmologic disorders [ 7 , 12 ], or neural crest tumors [ 7 ]. These abnormalities generate symptoms and may require specific treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Zaburzenia narządu wzroku. U chorych, głównie z mutacjami PARM, opisano zez, zaburzenia funkcji źrenicy (nieprawidłowe kurczenie i rozszerzanie się w odpowiedzi na bodziec świetlny lub jego brak) i tęczówki (atrofia tęczówki, szczątkowy mięsień zwieracz źrenicy (Patwari et al, 2012;Boulanger-Scemama et al, 2014).…”
Section: Objawy Zespołu Wrodzonej Centralnej Hipowentylacji (Cchs)unclassified